Description of the F-0 exuviae of Argia claussenii Selys, 1865 (Odonata: Coenagrionidae) - Dias-Oliveira, Tomás Matheus; Santos, Jean Carlos; Souza, Marcos Magalhães De; Vilela, Diogo Silva (Zootaxa, 2025)
Here we describe, illustrate and diagnose the F-0 exuviae of Argia claussenii Selys, 1865, collected in Minas Gerais state, Brazil (18°23’14.8” S, 43°18’14.3” W) between May and November 2024. It can be separated from other congeners by the morphology of the mandible, prementum and gonapophyses.